Impacto gerado na vida das mulheres removidas das favelas - Takeda, Akino (2014)
Interventions that seek to change the areas occupied by squatters have been one of the most common forms of Urban Management Policies, trying revolver one of the major problems of Brazilian metropolises, namely the precarious living conditions of a large part of the population in the city. A Pedreira Prado Lopes, a slum located in the northwestern region of Belo Horizonte, is one of twelve local benefit program by urbanization of slums Vila Viva, a program of structural intervention in Slums at the municipal level. These interventions, which are benefiting 9,000 residents have funds of R$37,4 millions the PAC (Growth Acceleration Program) and were guided by PGE - Specific Global Plan prepared by technicians URBEL (Urbanization Company of Belo Horizonte) in 1998. This project intervention was the creation of a set of housing for former slum housing. The objective of this research is to know how this intervention impacted the lives of residents after settling in condominiums, seeking to describe the changes on the horizon of women who are in most household heads residents of these buildings, as shown by studies of the IBGE (Brazilian Institute of Geography and Statistics), 2011